Prediction of simulated 1000 m kayak ergometer performance in young athletes - Rama, L.; Coelho, A.; Carrion-Balbuena, M. E.; Alves, F. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The competitive distance of 1000m-kayak effort is characterized by a large requirement of aerobic cardio-circulatory and respiratory system, and at the same time, a great ability to produce work through anaerobic lactic metabolic pathway. The performance of young athletes is also modulated by morphological and maturation status. This study aimed to evaluate the predictive value of cardiorespiratory fitness, anthropometric, maturation and biomechanical indicators to the performance in of 1000 meters in kayak ergometer in youn athletes. Methods: 12 young kayak athletes of Portuguese national level (16.0 ± 1.1 years old; 63.8 ± 7,2kg body mass; 174.9 ± 7,2cm; with 100,1 ± 5.7%% of mature height predicted; mean weekly training is 10.5 ± 2.4 hours, were submitted to two protocols in kayak ergometer (Dansprint,UK) with 48 hours apart. In the first visit to the laboratory, they accomplished a specific warm-up to familiarize with the ergometer (15`). After resting (10`) they underwent an incremental protocol starting 8 km/h with increments of 1 km/h each 2 minutes, until exhaustion. In the second visit to the laboratory at the same time of the day, they accomplished the same warm-up and rest interval and then they underwent a simulated maximal 1000m assuming the same approach as they use in competition. Results: In the incremental protocol a VO2 max of 3.4 ± 0.6 (L/min), a mechanical power of 138.5 ± 24.5 watts (MAP) at a speed of 13 ± 0.5 km/h (MAS) were reached. The first ventilatory threshold was held at 57,4±8,8% and the respiratory compensation point at 79,2±7,1% of VO2max. At the 1000m simulating the race 292.25 ± 15 seconds was spend, maintaining a mean speed of 97±2.8% of MAS and 90±6.5% and 95.7±16,6 of the VO2max and PAM respectively. Discussion: Important correlations were found between the performance in the 1000m and chronologically age, VO2max MAP, MAS, stroke frequency at VO2max, velocity at first ventilatory threshold and compensation respiratory point, and HR at Lv1. The final lactate accumulation confirmed the important contribution of lactic anaerobic (12.4 ± 2.4 mmol/L). The variation of results in 1000 meters in kayak ergometer was strongly associated to maximal aerobic power (MAP) and with stroke frequency at VO2mx. An estimated explanation regression model for performance (s) of 1000 meters in kayak ergometer was found to the performance on 1000m with the PAM and stroke frequency at VO2max speed. Time 1000m (s) = 413,378 - 0,433 (PAM) - 0,554 (SF at VO2max); R2 = 84.5%. The maximal aerobic power and the stroke frequency at this intensity seems to be an important strategy to monitor training adaptation, namely to predict performance in young kayakers.